ANALYSIS OF TRAINING, CAREER DEVELOPMENT, PROMOTION OF POSITION TO PERFORMANCE OF EMPLOYEES PD. PASAR BAUNTUNG BATUAH, BANJAR REGENCY KALIMANTAN SELATAN IN MARTAPURA - Abdus Sadiq (JURNAL KINDAI, 2020)
Abdus Sadiq, 1711322024534, Training Analysis, Career Development, Position Promotion of Employee Performance PD. Bauntung Batuah Market, Banjar Regency, South Kalimantan, in Martapura, under the guidance of Mr. Musthafa and Mr. Asruni, as supervisors I and II. This research was conducted with the aim to find out the training effect on the performance of employees PD. Bauntung Batuah Market, Banjar Regency, South Kalimantan in Martapura; to find out career development effect on the performance of employees. PD Bauntung Batuah Market, Banjar Regency, South Kalimantan in Martapura; to find out which promotion has an effect on the performance of employees PD. Bauntung Batuah Market, Banjar Regency, South Kalimantan in Martapura and to find out training, career development and job promotion simultaneously affect the performance of employees PD. Bauntung Batuah Market, Banjar Regency, South Kalimantan in Martapura. Analysis of the data used in this research is quantitative descriptive with a sample of 40 respondents and analyzed the data using multiple linear regression test. Based on the results of the study concluded that training has a significant effect on the performance of employees PD. Bauntung Batuah Market, Banjar Regency, South Kalimantan in Martapura; Career development influences the performance of employees PD. Bauntung Batuah Market, Banjar Regency, South Kalimantan in Martapura; Job promotions affect the performance of employees PD. Bauntung Batuah Market, Banjar Regency, South Kalimantan in Martapura; and training, career development and promotion simultaneously simultaneously have a very significant effect on the performance of employees PD. Bauntung Batuah Market, Banjar Regency, South Kalimantan in Martapura.Keywords: Training, Career development, Job promotion, Employee performance PD. Bauntung Market